Kajian Review Aplikasi Serat Sisal (Sisal Fiber) Sebagai Alternatif Komposit Polimer - Fauziah, Anis Khoirun Nisa Nur; Aritonang, Sovian; Murniati, Riri (Fakultas Teknik UMSU, 2024)
Sisal fiber is a natural fiber obtained from the sisal plant (agave sisalana). In addition to the low price of sisal fiber, its strength is legendary with its high tensile strength and superior stiffness. When used as reinforcement in polymer composites, these fibers can provide additional strength to the material. This makes the composite more resistant to compression, tension and bending. Because it has good strength and resistance to pressure, sisal fiber is often used as a reinforcement in making polymer composites. Sisal fiber is also often used in making ropes, nets, cables and other products that require mechanical resistance. The potential for using sisal fiber in various industries is very large. This fiber can be used as a composite for automotive materials, building construction materials, the shipping industry, other equipment, and even packaging. Sisal fiber shows excellent resilience and strength when tested together with other components. Therefore, sisal fiber has special properties and is often used as an alternative to natural fibers in polymer composites.